2020
DOI: 10.2147/ijnrd.s224871
|View full text |Cite
|
Sign up to set email alerts
|

<p>Factors Associated with Uremic Pruritus in Patients Undergoing Peritoneal Dialysis</p>

Abstract: Aim: The aim of this study was to investigate different intensities of uremic pruritus in the daytime and nighttime, as well as contributing factors, in patients undergoing peritoneal dialysis (PD). Methods: A total of 46 patients (31 males, 15 females) with a mean age of 59.4±14.7 years and mean PD vintage of 29.2±25.2 months were enrolled in this single-center, prospective, cross-sectional study. The intensity of uremic pruritus in the daytime and nighttime was assessed using a visual analog scale (VAS). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…92 Mathur et al 90 showed that mean worst itching intensity for enrolled patients was 59.9 mm using the 100 mm VAS. Scores were significantly higher for the 12-hour nighttime period than for the 12-hour daytime period, which corresponds with the research on patients undergoing PD conducted by Minato et al 95 Additionally, in DOPPS, a third of patients were most bothered by itch at night. 13 Apart from the time of day, there are many other factors that can affect the course of itch.…”
Section: Clinical Presentationsupporting
confidence: 88%
“…92 Mathur et al 90 showed that mean worst itching intensity for enrolled patients was 59.9 mm using the 100 mm VAS. Scores were significantly higher for the 12-hour nighttime period than for the 12-hour daytime period, which corresponds with the research on patients undergoing PD conducted by Minato et al 95 Additionally, in DOPPS, a third of patients were most bothered by itch at night. 13 Apart from the time of day, there are many other factors that can affect the course of itch.…”
Section: Clinical Presentationsupporting
confidence: 88%
“…Oral delivery of human ACE2 through the probiotic species Lactobacillus paracasei increased ACE activity in the serum and tissues of mice. Similar results can be obtained with the bacteria-derived B38-CAP enzyme (147,148). Recent research highlighted the role of mucin biopolymers as pivotal in regulating mucin production, which is implied in viral replication in the gut.…”
Section: Treatment Proposals Prebiotics and Probioticssupporting
confidence: 79%
“…There are limited studies on CKD-aP-related predictors in patients with PD, and the results were inconsistent across studies. 5,13,27,28 Therefore, among potential predictors that have been previously reported to be associated with CKD-aP in patients undergoing HD or PD (age, sex, diabetes mellitus (DM), dialysis vintage, WCSC, renal Kt/V, peritoneal Kt/V, total Kt/V, urine output, creatinine, urea nitrogen, Hb, ferritin, calcium, phosphorus, calcium-phosphorus product, β 2 microglobulin, α 1 microglobulin, C-reactive protein and BNP), variables with p < 0.2 in univariate linear regression analysis of VAS scores were also included. 1,3 8,10 13,27 29 TARC, eosinophil count, WCSC on the upper arm, phosphorus, calcium-phosphorus product and BNP were included as candidate independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…5,13,27,28 Therefore, among potential predictors that have been previously reported to be associated with CKD-aP in patients undergoing HD or PD (age, sex, diabetes mellitus (DM), dialysis vintage, WCSC, renal Kt/V, peritoneal Kt/V, total Kt/V, urine output, creatinine, urea nitrogen, Hb, ferritin, calcium, phosphorus, calcium-phosphorus product, β 2 microglobulin, α 1 microglobulin, C-reactive protein and BNP), variables with p < 0.2 in univariate linear regression analysis of VAS scores were also included. 1,3 8,10 13,27 29 TARC, eosinophil count, WCSC on the upper arm, phosphorus, calcium-phosphorus product and BNP were included as candidate independent variables. However, because a strong correlation between phosphorus and calcium-phosphorus product was observed, the calcium-phosphorus product was consequently excluded as an independent variable, given the multicollinearity.…”
Section: Methodsmentioning
confidence: 99%